BCG and BCG/DNAhsp65 Vaccinations Promote Protective Effects without Deleterious Consequences for Experimental Autoimmune Encephalomyelitis - Goncalves Zorzella-Pezavento, Sofia Fernanda [UNESP]; Fujiara Guerino, Clara Pires [UNESP]; Chiuso-Minicucci, Fernanda [UNESP]; Donega Franca, Thais Graziela [UNESP]; Watanabe Ishikawa, Larissa Lumi [UNESP]; Masson, Ana Paula; Silva, Celio Lopes; Sartori, Alexandrina [UNESP] (Hindawi Publishing Corporation, 2013)
A prime-boost strategy conserving BCG is considered the most promising vaccine to control tuberculosis. A boost with a DNA vaccine containing the mycobacterial gene of a heat shock protein (pVAXhsp65) after BCG priming protected mice against experimental tuberculosis. However, anti-hsp65 immunity could worsen an autoimmune disease due to molecular mimicry. In this investigation, we evaluated the effect of a previous BCG or BCG/pVAXhsp65 immunization on experimental autoimmune encephalomyelitis (EAE) development. Female Lewis rats were immunized with BCG or BCG followed by pVAXhsp65 boosters. The animals underwent EAE induction and were daily evaluated for weight loss and clinical score. They were euthanized during recovery phase to assess immune response and inflammatory infiltration at the central nervous system. Previous immunization did not aggravate or accelerate clinical score or weight loss. In addition, this procedure clearly decreased inflammation in the brain. BCG immunization modulated the host immune response by triggering a significant reduction in IL-10 and IFN-gamma levels induced by myelin basic protein. These data indicated that vaccination protocols with BCG or BCG followed by boosters with pVAXhsp65 did not trigger a deleterious effect on EAE evolution.